Study of fruits and seeds of Ipomoea teotitlanica McPherson (Convolvulaceae) - Murguia Sanchez, Guillermina; Marquez Guzman, Judith; Laguna Hernandez, Guillermo; Ponce Salazar, Margarita (Instituto de Ecología, A.C., 1995)
Ipomoea teotitlanica McPherson was described from an unique herbarium specimen without fruits and seeds. The environmental conditions of the type locality where Ipomoea teotitlanica is established and the structural features of its flowers, fruits and seeds are described here. The morphology of fruit and seed corresponds to that described for the Arborescentes group: coriaceous sepals, dehiscent fruit and seed with long marginal trichomes.